Ageism as social pathology in geriatric medicine - Andrei, Ilnitski; Kiryl, Prashchayeu (Magyar Gerontológia, 2023)
The main trend of modern geriatrics is to maintain a high functional ability, which consists of intrinsic capacity and environment. It is important to attach importance to the impact of the environment, including of its social component, when can promote the development of social pathology, for example loneliness or the consequences of ageism which can significantly reduce the quality of life.